Pay inequality and the deteriorating labour standards in Croatia - Rubinić, Ivan (Array, 2019)
This study furnishes proof in support of the hypothesis that Croatian employees are experiencing persistent worsening of the labour standard alongside the rising divergence in their earnings distribution. The research disclosed five mutually reinforcing tendencies investigated through a widely used Theil index and functional income distribution. The empirical analysis demonstrated the deterioration of the labour standard apparent through the continuous decline in the labour share of income concurrent with productivity growth. The net pay inequality reported a radical increase and stabilization on a higher plane with a nominal improvement brought about as a result of the layoffs predominantly affecting the lower tail of the distribution. Consequently, the lesser earning dispersion came at the expense of the overall rise in inequality. The gross inequality indicated an increasing pattern highly and positively correlated with the movement of the highest earners experiencing a triple-digit population surge. The rising between-county pay inequality throughout the period suggested a strong bias toward excessive centralization, evident with the capital city being the exclusive county consistently reporting above-average earning levels. Lastly, the between-sector pay inequality exhibited an overall decline. This isolated case, however, remains a dominant driver of inequality, given that the lowesthighest earning sector range is approximately double that of the between-county range. These findings are detrimental to the Croatian worker’s wellbeing and they pose a challenge to the national policymakers who must counter adverse tendencies in order to circumvent the current exodus of skilled workers, and restore long-term macroeconomic stability.